Molecular Analysis of Oxacillinase Genes in MDR Strain of Acinetobacter baumannii Isolated in Clinical Samples from North India - Pandey, Anand Kumar; Siddiqui, Areena Hoda; Saquib, Mohd; Srivastava, Vipul Kumar; Tiwari, and Neha (Journal of Neonatal Surgery, 2025)
Background: Acinetobacter baumannii is a ubiquitous coccobacillus which is currently a topic of great concern due to its high level of drug resistance to almost all classes of antimicrobials. Due to this it results in high level of morbidity and mortality in hospitalizedpatients especially in critical care areas. This opportunistic pathogen in short span of time has acquired high level of resistance against carbapenem which are one of the last resorts in our antimicrobial arsenal. Aim and Objective: To study the molecular analysis of oxacillinase genes in MDR strain of Acinetobacter baumannii isolated in clinical samples from North India. Material and Methods: Clinical samples received for bacterial culture and antimicrobial sensitivity testing were inoculated and incubated for 24-48 hours at 37°C. For blood culture incubation was done for 5 days in blood culture bottle. Bacterial identification and antimicrobial sensitivity were done by Vitek®2, bioMérieux. Antimicrobial Sensitivity of A. baumanniiisolated was recorded and multi drug resistant isolates were preserved for Polymerase chain reaction(PCR) to detect the presence ofbeta lactam OxacillinaseblaOXA 51 and blaOXA58 genes. Results: A total of 2644 samples were processed during the study period from 30th April,2022 to 20th October,2024. 920 samples were culture positive. Out of 920 bacterial isolates, 88 were A. baumannii and 84 out of these were Carbapenem Resistant A. baumannii(CRAB). 30 CRAB isolates were selected for PCR and all showed presence of blaOXA 51 gene while none of the isolates harbored blaOXA 58 gene. Conclusions: There is an increased isolation rate of A. baumannii from clinical samples and more than 95% isolates of A. baumannii are CRAB. All the CRAB isolates tested by PCR showed presence of blaOXA 51 gene and none had the presence of blaOXA 58 gene. Management of A. baumannii infections is a challenge. In the current scenario proper implementation of Hospital Infection Control policies and adherence to antimicrobial stewardship policies as preventive strategies should be our priority.